Steady State Errors
Steady State Errors
Steady State Errors
11
Lecture 1
Steady State Errors
We define the error as the difference between the
input and output:
(1)
12
s2 +7s+10
1
s2 + 7s + 5
E(s) = (1 T (s)) =
s
s(s2 + 7s + 10)
13
14
Note that
E(s) = R(s) C(s)
and
C(s) = E(s)G(s)
which yield
E(s) =
R(s)
1 + G(s)
1
s
s 1s
1
e() = lim
=
s0 1 + G(s)
1 + lims0 G(s)
15
s0
1
s2
1
s s12
=
e() = lim
s0 1 + G(s)
lims0 sG(s)
To have zero steady state error
lim sG(s) =
s0
1
s3
s s13
1
e() = lim
=
s0 1 + G(s)
lims0 s2G(s)
To have zero steady state error
lim s2G(s) =
s0
16
(s + z1)(s + z2)...
sn(s + p1)(s + p2)...
n3
17
Examples
Consider the System (with no integrator) in the
following figure
5
)
s2
18
Examples
Consider the System (with one integrator) in the
following figure
5
)
s2
5
5
1
s s52
=
=
=
e() = lim
s0 1 + G(s)
lims0 sG(s) 100 20
The steady state error for r(t) = 5t2u(t) (R(s) =
10
)
s3
s 10
10
10
s3
e() = lim
=
=
=
2
s0 1 + G(s)
lims0 s G(s)
0
19
{z
Kv
1 10
{z
Ka
1 11
Kp = lim G(s)
s0
1
1+Kp .
Velocity constant
Kv = lim sG(s)
(2)
s0
1
KV .
Acceleration constant
Ka = lim s2G(s)
s0
(3)
1
Ka .
1 12
Example
Given the control system
1
= 0.1
Kv
5K
Kv = 10 = lim sG(s) =
s0
678
we obtain K = 672
1 13